The Impact of Intellectual Capital on Strategic Leadership: A Field Study in Yemeni Community Colleges (Sana'a) (International Journal of Financial, Administrative and Economic Sciences, 2026)
The study aimed to identify the impact of intellectual capital, with its dimensions (human capital, structural capital, and relational capital), on achieving strategic entrepreneurship with its dimensions (creativity, entrepreneurial culture, risk-taking, competitive advantage, and strategic resource management) in Yemeni community colleges in the capital city of Sana’a. The study adopted the descriptive–analytical approach. The study population comprised employees of Yemeni community colleges under study, totaling (1,132) employees across (11) private community colleges in the capital Sana’a, while the random sample size reached (390) respondents. A questionnaire was designed to collect data, and the data were analyzed and the hypotheses tested using the Statistical Package for the Social Sciences (SPSS 28). The results revealed a high level of both intellectual capital and strategic entrepreneurship in the community colleges under study. The findings also indicated a positive and statistically significant effect of intellectual capital on strategic entrepreneurship. Moreover, the relational capital dimension had the strongest effect on achieving strategic entrepreneurship, followed by structural capital, whereas the human capital dimension did not show a positive statistically significant effect in the multiple regression model. Regarding the dimensions of strategic entrepreneurship, the competitive advantage dimension achieved the highest mean, while the risk-taking dimension recorded the lowest mean, although it remained at a high level. The study recommended that leaders of Yemeni community colleges focus on supporting and developing intellectual capital in its various dimensions, particularly by strengthening institutional relationship networks, developing organizational structures, and fostering an organizational culture that supports creativity and calculated risk-taking, thereby enhancing the strategic entrepreneurial orientation.
Keywords: Intellectual Capital; Strategic Entrepreneurship; Community Colleges; Sana'a; Yemen